(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Elderberry (Sambucus nigra) is one of the important multiuse plants in the world. There is no studies about this shrub in Syria. In this study, information about this plant was collected from two sections: first in the whole world with collecting environmental needs and information about international distribution and abundance. In second way, sites that looked appropriate by using information from first section were chosen for looking about elderberry in Syria. Information, samples, photos, evidences and witnesses have been investigated for the first time about this species in Syria. Aleppo (City of Aleppo & Afrin province), Idlib, Homs and Damascus were sites have individuals in natural or cultivated form of this plant. Lattakia and Tartus didn’t have any evidence of this plant. As a result of this study a predicted map of Sambucus nigra distribution was putted for Syria and collected information about this plant can help in future researches in Syria.